Firm Specific Determinants of Stock Market Price of Nepalese Enterprises - Shrestha, Purna Man (Journal of Nepalese Management and Research, 2022)
This paper aims to identify the firm-specific determinants of stock market price of Nepalese enterprises. For this purpose, this paper has used the unbalanced panel data of 47 firms listed in NEPSE for the period of 1994 to 2019. Breusch and Pagan Lagrangian multiplier test and Hausman test is used to select appropriate regression model. Both tests concluded that Fixed Effect model is appropriate for the given set of data. The result reveals that firm-specific factors play significant role to determine market price per share of Nepalese enterprises. Further, the result concludes that there is a significant positive influence of firm size [Ln (ME)], dividend per share (DPS) and earnings per share (EPS), and negative influence of return on equity (ROE), and dividend yield (DY) on market price per share of Nepalese enterprises. Similarly, an insignificant positive influence of book value per share (BVPS) and an insignificant negative of influence return on assets (ROA) on market price of share are observed.